Amelioration of systemic inflammation in advanced chronic liver disease upon beta-blocker therapy translates into improved clinical outcomes. Issue 9 (16th November 2020) - Jachs, Mathias; Hartl, Lukas; Schaufler, Dunja; Desbalmes, Christopher; Simbrunner, Benedikt; Eigenbauer, Ernst; Bauer, David Josef Maria; Paternostro, Rafael; Schwabl, Philipp; Scheiner, Bernhard; Bucsics, Theresa; Stättermayer, Albert Friedrich; et al.
Abstract : Objective: Systemic inflammation promotes the development of clinical events in patients with advanced chronic liver disease (ACLD). We assessed whether (1) non-selective beta blocker (NSBB) treatment initiation impacts biomarkers of systemic inflammation and (2) whether these changes in systemic inflammation predict complications and mortality. Design: Biomarkers of systemic inflammation, that is, white blood cell count (WBC), C reactive protein (CRP), interleukin-6 (IL-6) and procalcitonin (PCT) were determined at sequential hepatic venous pressure gradient (HVPG) measurements without NSBB and under stable NSBB intake. The influence of NSBB-related changes in systemic inflammation on the risk of decompensation and liver-related death was analysed using competing risk regression. Results: Our study comprised 307 stable patients with ACLD (Child-A: 77 (25.1%), Child-B: 161 (52.4%), Child-C: 69 (22.5%), median HVPG: 20 (IQR 17–24) mm Hg) including 231 (75.2%) with decompensated disease. WBC significantly decreased upon NSBB therapy initiation (median: −2 (IQR −19;+13)%, p=0.011) in the overall cohort. NSBB-related reductions of WBC (Child-C: −16 (−30;+3)% vs Child-B: −2 (−16;+16)% vs Child-A: +3 (−7;+13)%, p<0.001) and of CRP (Child-C: −26 (−56, +8)% vs Child-B: −16 (−46;+13)% vs Child-A: ±0 (−33;+33)%, p<0.001) were more pronounced in advanced stages of cirrhosis. The NSBB-associated changes in WBC correlated with changes in CRP (Spearman's ρ=0.228, p<0.001), PCT (ρ=0.470, p=0.002) and IL-6 (ρ=0.501, p=0.001), but not with changes in HVPG (ρ=0.097, p=0.088). An NSBB-related decrease in systemic inflammation (ie, WBC reduction ≥15%) was achieved by n=91 (29.6%) patients and was found to be an independent protective factor of further decompensation (subdistribution HR, sHR: 0.694 (0.49–0.98), p=0.038) in decompensated patients and of liver-related mortality in the overall patient cohort (sHR: 0.561 (0.356–0.883), p=0.013). Conclusion: NSBB therapy seems to exert systemic anti-inflammatory activity as evidenced by reductions of WBC and CRP levels. Interestingly, this effect was most pronounced in Child-C and independent of HVPG response. An NSBB-related WBC reduction by ≥15% was associated with a decreased risk of further decompensation and death.